Attitudes and health behaviors of middle-aged and older adults with elevated tumor markers in China - Yu, Renke; Xu, Zhijie; Lu, Yiting; Zhu, Yue; Chen, Liying (Frontiers in Psychology, 2024)
Objectives To understand the attitudes and health behaviors of middle-aged and older adults in China after receiving elevated results of tumor markers (TMs) test in the annual health examinations (AHEs) and explore the influencing factors. Design A three-section online questionnaire survey was conducted from March 1 to April 30, 2020. It included items on participants' sociodemographic features, attitudes, and health behaviors. Setting and Participants Participants were aged 45 and older and had at least one elevated result on four types of TMs in the AHEs in Sir Run Run Shaw Hospital,